Cured product for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

By using water-soluble polymers, crosslinking agents and cured products of cellulose nanofibers in lithium-ion secondary batteries, the problem of reducing circulation characteristics of lithium-ion secondary batteries is solved, and a higher circulation characteristics and capacity maintenance rate is achieved.

CN119856301APending Publication Date: 2025-04-18TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380065504.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-06-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the circulation process, the circulation characteristics of the existing lithium-ion secondary batteries are reduced due to the volume expansion of the negative electrode active material.

Method used

A cured substance containing water-soluble polymer, a crosslinking agent and cellulose nanofibers is used as the curing agent for lithium-ion secondary batteries. The crosslinking agent is used to form a crosslinking structure between these components, thereby improving the circulation characteristics of the battery.

Benefits of technology

By using this cured product, the circulation characteristics of the lithium-ion secondary battery are significantly improved, and a high capacity maintenance rate can be maintained after 200 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856301A_ABST
    Figure CN119856301A_ABST
Patent Text Reader

Abstract

This cured product for lithium ion secondary batteries comprises a water-soluble polymer, a crosslinking agent, and cellulose nanofibers. The crosslinking agent crosslinks different water-soluble polymers or between the water-soluble polymer and the cellulose nanofibers. When a wide-angle X-ray scattering (WAXS) measurement using a CuK [alpha] ray is performed, a peak is present in a range in which a diffraction angle 2 [theta] is 16-21 degrees inclusive. The peak width at half maximum of the peak is 5.5 DEG or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cured product for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. This application claims priority based on Japanese Patent Application No. 2022-145039 filed in Japan on September 13, 2022, and the contents are incorporated herein by reference. Background Art

[0002] Lithium-ion secondary batteries are also widely used as a power source for mobile devices such as mobile phones and notebook computers, and hybrid vehicles.

[0003] The capacity of lithium-ion secondary batteries depends mainly on the active material of the electrode. Graphite is often used as the negative electrode active material, and a negative electrode active material with a higher capacity than graphite is sought. Therefore, silicon (Si), which has a much larger theoretical capacity than graphite (372 mAh / g), has attracted much attention.

[0004] The negative electrode active material containing Si is accompanied by a large volume expansion during charging. The volume expansion of the negative electrode active material becomes the reason for the reduction of the cycle characteristics of the battery. When the volume expansion of the negative electrode active material occurs, for example, there are cases where cracks occur in the negative electrode active material, the interface between the negative electrode active material layer and the collector is peeled off, or the SEI (Solid Electrolyte Interphase) coating is cracked and the electrolyte is decomposed. This will reduce the cycle characteristics of the battery.

[0005] For example, Patent Document 1 describes a slurry composition containing a carboxymethyl group-containing cellulose ether and cellulose nanofibers. Patent Document 1 describes that when cellulose nanofibers and a rubber component are combined, the electrode becomes flexible and the cycle characteristics of the battery are improved.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2018 / 135352 Summary of the invention

[0009] The technical problem that the invention is intended to solve

[0010] Seeking further improvement in cycle characteristics.

[0011] The present disclosure has been made in view of the above-mentioned technical problems, and an object of the present disclosure is to provide a cured product for lithium ion secondary batteries that can improve the cycle characteristics of lithium ion secondary batteries.

[0012] Means for solving technical problems

[0013] In order to solve the above technical problems, the following means are provided.

[0014] (1) The first embodiment provides a solidified material for lithium ion secondary batteries having a water-soluble polymer, a crosslinking agent, and cellulose nanofibers. The crosslinking agent crosslinks different water-soluble polymers or the water-soluble polymer and the cellulose nanofibers. The solidified material for lithium ion secondary batteries has a peak in a range where the diffraction angle 2θ is greater than 16° and less than 21° when subjected to wide-angle X-ray scattering (WAXS) measurement using CuKα rays. The half-peak width of the peak is less than 5.5°.

[0015] (2) In the cured product for lithium ion secondary battery of the above embodiment, the water-soluble polymer may be at least one selected from polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, a copolymer of acrylic acid and vinyl alcohol, and polyacrylic acid.

[0016] (3) In the cured product for lithium ion secondary battery of the above embodiment, the crosslinking agent may be a compound obtained by dissociating a blocking agent from any one selected from blocked isocyanate silane compounds, blocked diisocyanate compounds, and blocked triisocyanate compounds; or a titanium compound.

[0017] (4) In the cured product for lithium ion secondary batteries of the above embodiment, the weight average molecular weight of the water-soluble polymer may be 9,000 or more and 200,000 or less.

[0018] (5) A second aspect provides a negative electrode for a lithium ion secondary battery comprising a negative electrode active material and the cured product for a secondary battery of the above aspect.

[0019] (6) A third aspect provides a lithium ion secondary battery comprising: the negative electrode for lithium ion secondary battery of the above aspect; a positive electrode; and a separator located between the negative electrode for lithium ion secondary battery and the positive electrode.

[0020] Effects of the Invention

[0021] The cured product for lithium ions of the above embodiment improves the cycle characteristics of lithium ion secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the lithium ion secondary battery according to the first embodiment.

[0023] Figure 2 It is a schematic diagram of the adhesive agent involved in the first embodiment.

[0024] Figure 3 This is a schematic diagram of the pressure-sensitive adhesive according to the first embodiment before cross-linking.

[0025] Figure 4This is an example of wide-angle X-ray scattering (WAXS) measurement results of the adhesive agent and the like according to the first embodiment.

[0026] Explanation of symbols

[0027] 1 Adhesive

[0028] 2 Water-soluble polymers

[0029] 3 Cross-linking agent

[0030] 4 Cellulose nanofibers

[0031] 5 Cross-linking Precursors

[0032] 10 Diaphragm

[0033] 20 Positive electrode

[0034] 22. Positive electrode collector

[0035] 24 Positive electrode active material layer

[0036] 30 Negative electrode

[0037] 32 Negative electrode collector

[0038] 34 Negative electrode active material layer

[0039] 40 Power generation element

[0040] 50 outer body

[0041] 52 metal foil

[0042] 54 Resin layer

[0043] 60, 62 terminals

[0044] 100 Lithium-ion secondary battery DETAILED DESCRIPTION

[0045] The following description will describe the embodiments in detail with reference to the accompanying drawings as appropriate. In the drawings used in the following description, in order to facilitate the understanding of the features, the features are sometimes enlarged for convenience, and the size ratios of the components are sometimes different from the actual ones. The materials, dimensions, etc. illustrated in the following description are only examples, and the present invention is not limited thereto, and can be implemented by appropriately changing them within the scope of not changing the main purpose.

[0046] "Lithium-ion secondary battery"

[0047] Figure 1 It is a schematic diagram of the lithium ion secondary battery of the first embodiment. Figure 1The lithium ion secondary battery 100 shown includes a power generation element 40, an outer casing 50, and a non-aqueous electrolyte (not shown). The outer casing 50 surrounds the power generation element 40. The power generation element 40 is connected to the outside via a pair of terminals 60 and 62 connected to the power generation element 40. The non-aqueous electrolyte is contained in the outer casing 50. Figure 1 Although the case where one power generation element 40 is contained in the outer casing 50 is illustrated, a plurality of power generation elements 40 may be stacked in the outer casing 50. The lithium ion secondary battery 100 may be cylindrical, rectangular, stacked, or button-shaped.

[0048] (Power generation element)

[0049] The power generating element 40 includes a separator 10 , a positive electrode 20 , and a negative electrode 30 .

[0050] <Positive electrode>

[0051] The positive electrode 20 includes, for example, a positive electrode current collector 22 and a positive electrode active material layer 24 . The positive electrode active material layer 24 is in contact with at least one surface of the positive electrode current collector 22 .

[0052] [Positive electrode collector]

[0053] The positive electrode current collector 22 is, for example, a conductive plate. The positive electrode current collector 22 is, for example, a thin metal plate such as aluminum, copper, nickel, titanium, or stainless steel. Lightweight aluminum is preferably used for the positive electrode current collector 22. The average thickness of the positive electrode current collector 22 is, for example, not less than 10 μm and not more than 30 μm.

[0054] [Positive electrode active material layer]

[0055] The positive electrode active material layer 24 contains, for example, a positive electrode active material, and may contain a conductive auxiliary agent and a binder as necessary.

[0056] The positive electrode active material includes an electrode active material that can reversibly perform absorption and release of lithium ions, extraction and insertion (intercalation) of lithium ions, or doping and dedoping of lithium ions and counter anions.

[0057] The positive electrode active material is, for example, a composite metal oxide. Composite metal oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), and LiNiO2. x Co y Mn z M aO2 compounds (in the general formula, x+y+z+a=1, 0≤x<1, 0≤y<1, 0≤z<1, 0≤a<1, M is one or more elements selected from Al, Mg, Nb, Ti, Cu, Zn, Cr), lithium vanadium compounds (LiV2O5), olivine-type LiMPO4 (wherein M represents one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, Zr or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9<x+y+z<1.1). The positive electrode active material may also be an organic substance. For example, the positive electrode active material may also be polyacetylene, polyaniline, polypyrrole, polythiophene, or polyacene.

[0058] The positive electrode active material may also be a material that does not contain lithium. Examples of materials that do not contain lithium include FeF3, conjugated polymers containing organic conductive substances, Chevrel phase compounds, transition metal chalcogenides, vanadium oxides, niobium oxides, and the like. Materials that do not contain lithium may use only any one material, or may use a combination of multiple materials. In the case where the positive electrode active material is a material that does not contain lithium, for example, discharge is performed first. By discharging, lithium is inserted into the positive electrode active material. In addition, the positive electrode active material may also be chemically or electrochemically pre-doped with lithium for the material that does not contain lithium.

[0059] The conductive additive improves the electronic conductivity between the positive electrode active materials. The conductive additive is, for example, carbon powder, carbon nanotubes, carbon materials, metal powder, a mixture of carbon materials and metal powder, and conductive oxides. Carbon powder is, for example, carbon black, acetylene black, Ketjen black, etc. Metal powder is, for example, powder of copper, nickel, stainless steel, iron, etc.

[0060] The content of the conductive additive in the positive electrode active material layer 24 is not particularly limited. For example, the content of the conductive additive relative to the total mass of the positive electrode active material, the conductive additive, and the binder is 0.5 mass % to 20 mass %, preferably 1 mass % to 5 mass %.

[0061] The binder in the positive electrode active material layer 24 binds the positive electrode active materials to each other. A known binder can be used as the binder. In addition, the binder can also be the same binder as the binder used for the negative electrode active material layer 34 described later. The binder is preferably insoluble in the electrolyte, has antioxidant properties, and has adhesive properties. The binder is, for example, a fluororesin. The binder is, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid and its copolymers, metal ion crosslinked bodies of polyacrylic acid and its copolymers, polypropylene (PP) or polyethylene (PE) grafted with maleic anhydride, and mixtures thereof. The binder used for the positive electrode active material layer is particularly preferably PVDF.

[0062] The content of the binder in the positive electrode active material layer 24 is not particularly limited. For example, the content of the binder relative to the total mass of the positive electrode active material, the conductive aid, and the binder is 1% by mass or more and 15% by mass or less, preferably 1.5% by mass or more and 5% by mass or less. When the content of the binder is small, the bonding strength of the positive electrode 20 is weakened. Because the binder is not electrochemically active and does not contribute to the discharge capacity, when the content of the binder is high, the energy density of the lithium ion secondary battery 100 is reduced.

[0063] <Negative electrode>

[0064] The negative electrode 30 includes, for example, a negative electrode current collector 32 and a negative electrode active material layer 34. The negative electrode active material layer 34 is formed on at least one surface of the negative electrode current collector 32. The negative electrode 30 is an example of a negative electrode for a lithium ion secondary battery.

[0065] [Negative electrode current collector]

[0066] The negative electrode current collector 32 is, for example, a conductive plate material. The negative electrode current collector 32 can be the same as the positive electrode current collector 22 .

[0067] [Negative Electrode Active Material Layer]

[0068] The negative electrode active material layer 34 contains a negative electrode active material and a binder. The negative electrode active material layer 34 may contain a conductive additive as required. The binder is an example of a cured material for a lithium ion secondary battery.

[0069] The negative electrode active material contains silicon or a silicon compound. The silicon compound is, for example, a silicon alloy, silicon oxide, etc. For example, silicon or a silicon compound may be crystalline, amorphous, or a compound in which crystalline is dispersed in an amorphous state. Amorphous silicon or a silicon compound can be produced by melt spinning, gas atomization, etc. The negative electrode active material may also be a known substance other than silicon or a silicon compound.

[0070] Silicon alloy with X n Si represents. X is a cation. X is, for example, Ba, Mg, Al, Zn, Sn, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Y, Zr, Nb, Mo, W, Au, Ti, Na, K, etc. n satisfies 0≤n≤0.5. Silicon oxide is SiO x x satisfies, for example, 0.8≤x≤2. Silicon oxide may consist of only SiO2, may consist of only SiO, or may be a mixture of SiO and SiO2. In addition, oxygen may be partially absent in silicon oxide.

[0071] The negative electrode active material may also be a composite of silicon or a silicon compound. The composite is a structure in which a conductive material is coated on at least a portion of the surface of particles of silicon or silicon compounds. Conductive materials are, for example, carbon materials, Al, Ti, Fe, Ni, Cu, Zn, Ag, Sn, etc. For example, a silicon-carbon composite material (Si-C) is an example of a composite. Relative to the total mass of the composite, the coating amount of the conductive material relative to the silicon or silicon compound particles is, for example, 0.01 mass % or more and 30 mass % or less, preferably 0.1 mass % or more and 20 mass % or less. The composite can be made, for example, by mechanical alloying, chemical vapor deposition, wet method, a method of carbonizing the polymer by thermal decomposition of the polymer after coating the polymer, etc.

[0072] The specific surface area of ​​the negative electrode active material determined by the BET method is, for example, 0.5 m 2 / g or more and 100m 2 / g or less, preferably 1.0m 2 / g or more and 20m 2 When the specific surface area is small, it is difficult for Li ions to be inserted into or released from the negative electrode active material. When the specific surface area is large, a lot of binder is required for electrode polarization, and the capacity per unit volume of the lithium ion secondary battery is reduced.

[0073] The binder binds the negative electrode active materials to each other and to the negative electrode current collector. Figure 2 This is a schematic diagram of the adhesive 1 according to the first embodiment. The adhesive 1 includes a water-soluble polymer 2 , a crosslinking agent 3 , and cellulose nanofibers 4 .

[0074] The water-soluble polymer 2 is, for example, a polymer having a hydroxyl group. The water-soluble polymer 2 is, for example, polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, a copolymer of acrylic acid and vinyl alcohol, a copolymer of sodium acrylate and vinyl alcohol, sodium hydroxymethyl cellulose, polynorbornene dicarboxylic acid, and polyacrylic acid. The water-soluble polymer 2 is preferably polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, a copolymer of acrylic acid and vinyl alcohol, and polyacrylic acid. The copolymer of acrylic acid and vinyl alcohol is, for example, obtained by copolymerizing vinyl ester and ethylene unsaturated carboxylic acid ester and acidifying and hydrolyzing the copolymer. The water-soluble polymer 2 can be used alone or in combination.

[0075] The weight average molecular weight of the water-soluble polymer 2 is, for example, greater than 9000 and less than 200000. In particular, when polyvinyl alcohol is used as the water-soluble polymer 2, the weight average molecular weight is preferably greater than 9000 and less than 200000. A water-soluble polymer 2 with a small molecular weight cannot form a sufficient network structure of the adhesive 1 due to a small number of crosslinking points, and the elasticity of the adhesive 1 is reduced. When the molecular weight of the water-soluble polymer 2 is large, the adhesive 1 will gel and it is difficult to disperse evenly. In the case where the water-soluble polymer 2 before crosslinking can be obtained, the water-soluble polymer before crosslinking is analyzed to obtain the weight average molecular weight of the water-soluble polymer 2. In the case where the water-soluble polymer 2 before crosslinking cannot be obtained, the weight average molecular weight of the water-soluble polymer 2 can be roughly estimated based on the weight average molecular weight of the adhesive 1 and the presence ratio of the water-soluble polymer 2, the crosslinking agent 3 and the cellulose nanofiber 4 in the adhesive 1.

[0076] When polyvinyl alcohol is used as the water-soluble polymer 2, it is preferred to use partially saponified polyvinyl alcohol or completely saponified polyvinyl alcohol made of saponified polyvinyl acetate. Examples of polyvinyl alcohol include vinyl alcohol-vinyl acetate copolymers, vinyl alcohol-vinyl butyral copolymers, and ethylene-vinyl alcohol copolymers, preferably vinyl alcohol-vinyl acetate copolymers.

[0077] The copolymerization ratio of polyvinyl alcohol is represented by a saponification degree. The saponification degree of polyvinyl alcohol is, for example, 60 mol% or more and 99 mol% or less. When the saponification degree of polyvinyl alcohol is 60 mol% or more, it is easy to crosslink with the crosslinking agent 3. The saponification degree of polyvinyl alcohol can be obtained by the alkali consumption required for the hydrolysis of copolymerization units such as vinyl acetate or by composition analysis by NMR.

[0078] Here, whether the polymer is "water-soluble" can be determined by the following steps. First, prepare a mixture obtained by adding 1 part by weight of the polymer (equivalent to the solid content) to every 100 parts by weight of ion exchange water and stirring. The mixture is adjusted to a temperature of 20 to 95°C and a pH of 3 to 12 (NaOH aqueous solution and / or HCl aqueous solution are used for pH adjustment). Next, the mixture is passed through a 250-mesh sieve. In the case where the weight of the solid content of the residue that has not passed through the sieve and remains on the sieve does not exceed 50% by weight relative to the solid content of the added polymer, the polymer can be said to be water-soluble. It should be noted that even if the mixture of the above-mentioned polymer and water is in an emulsion state that separates into two phases when standing, as long as the above definition is met, the polymer is also water-soluble.

[0079] The crosslinking agent 3 crosslinks the water-soluble polymers 2 with each other and between the water-soluble polymers 2 and the cellulose nanofibers 4 .

[0080] The crosslinking agent 3 is, for example, a compound obtained by dissociating a blocking agent from any one selected from a blocked isocyanate silane compound, a blocked diisocyanate compound, and a blocked triisocyanate compound, or a titanium compound. Figure 2 The crosslinking agent 3 shown is a titanium compound.

[0081] The titanium compound contains titanium element in its structure. The titanium compound is an organic titanium compound, for example, a titanium chelate. The titanium compound may also be, for example, titanium lactate, triethanolamine titanium, ammonium lactate titanium, diethanolamine titanium, aminoethylaminoethanol titanium, etc. The titanium compound is a crosslinking agent that connects the water-soluble polymer 2. The titanium compound is a small crosslinking agent and is not easy to disintegrate the crystallinity of the water-soluble polymer 2.

[0082] The active isocyanate groups of the blocked isocyanate silane compound, the blocked diisocyanate compound and the blocked triisocyanate compound are protected by a blocking agent. The blocked isocyanate silane compound, the blocked diisocyanate compound and the blocked triisocyanate compound are kept stable by protecting the active isocyanate groups with a blocking agent under normal conditions, and the blocking agent is dissociated by heat treatment. The blocking agent is, for example, phenol, alcohol, oxime, lactam, etc.

[0083] As for the diisocyanate compound, for example, there can be mentioned aromatic diisocyanates having a carbon number of 6 or more and 20 or less (excluding the carbon in the NCO group, the same below), aliphatic diisocyanates having a carbon number of 2 or more and 18 or less, alicyclic diisocyanates having a carbon number of 4 or more and 15 or less, aromatic aliphatic diisocyanates having a carbon number of 8 or more and 15 or less, modified forms of these diisocyanates (carbodiimide modified forms, urethane modified forms, uretdione modified forms, etc.), and mixtures of two or more thereof.

[0084] Examples of the aromatic diisocyanate include 1,3- and / or 1,4-phenylene diisocyanate, 2,4- and / or 2,6-toluene diisocyanate, m-xylylene diisocyanate, 2,4′- and / or 4,4′-diphenylmethane diisocyanate (hereinafter, diphenylmethane diisocyanate is abbreviated as MDI), 4,4′-diisocyanate biphenyl, 3,3′-dimethyl-4,4′-diisocyanate biphenyl, 3,3′-dimethyl-4,4′-diisocyanate diphenylmethane, and 1,5-naphthalene diisocyanate.

[0085] Examples of the aliphatic diisocyanate include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, methyl 2,6-diisocyanatohexanoate, bis(2-isocyanatoethyl)carbonate, and 2-isocyanatoethyl-2,6-diisocyanatohexanoate.

[0086] Alicyclic diisocyanates include, for example, isophorone diisocyanate, dicyclohexylmethane-4,4′-diisocyanate, cyclohexane diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexylene diisocyanate, bis(2-isocyanateethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- and / or 2,6-norbornane diisocyanate.

[0087] The aromatic aliphatic diisocyanate is, for example, m- and / or p-xylylene diisocyanate, α,α,α′,α′-tetramethylene xylylene diisocyanate.

[0088] The triisocyanate compound has, for example, three isocyanate groups.

[0089] For example, the following chemical formulas (1-1) to (1-7) are examples of triisocyanates.

[0090]

[0091]

[0092] In addition, the triisocyanate may also be a compound having a biuret structure represented by the following chemical formula (1-8). The compound having a biuret structure represented by the chemical formula (1-8) is formed by urea and an isocyanate group. In the formula (1-8), R is a group obtained by removing an isocyanate group from a diisocyanate monomer.

[0093]

[0094] Figure 3Schematic diagram showing the adhesive before crosslinking of the first embodiment. The adhesive 1' before crosslinking comprises a water-soluble polymer 2, a crosslinking precursor 5, and cellulose nanofibers 4. The crosslinking precursor 5 is a crosslinking agent before crosslinking.

[0095] Figure 3 The crosslinking precursor 5 shown is a titanium compound. The crosslinking precursor 5 may be at least one selected from a blocked isocyanate silane compound, a blocked diisocyanate compound, and a blocked triisocyanate compound.

[0096] like Figure 3 As shown, in the case where the cross-linking precursor 5 is a titanium compound, the water-soluble polymer 2 and the cross-linking agent 3 are cross-linked by reacting the hydroxyl group of the water-soluble polymer 2 with the hydroxyl group of the titanium compound. In addition, the cellulose nanofibers 4 and the cross-linking agent 3 are cross-linked by reacting the hydroxyl group attached to the surface of the cellulose nanofiber 4 with the hydroxyl group of the titanium compound. The cross-linking reaction is not limited to the reaction between hydroxyl groups. For example, the alkoxy group of the titanium compound can also be detached and react with the hydroxyl group of the water-soluble polymer 2 or the cellulose nanofiber 4. In addition, the isocyanate group, carboxyl group, etc. of the titanium compound and the hydroxyl group of the water-soluble polymer 2 or the cellulose nanofiber 4 can also react.

[0097] In addition, when the crosslinking precursor 5 is any one selected from a blocked isocyanate silane compound, a blocked diisocyanate compound, and a blocked triisocyanate compound, the water-soluble polymer 2 and the crosslinking agent 3 are crosslinked by the reaction between the hydroxyl group of the water-soluble polymer 2 and the active isocyanate group. In addition, the cellulose nanofibers 4 and the crosslinking agent 3 are crosslinked by the reaction between the hydroxyl group attached to the surface of the cellulose nanofibers 4 and the active isocyanate group.

[0098] A part of the hydroxyl groups of the water-soluble polymer 2 does not react with the crosslinking precursor 5 and remains unreacted. The remaining hydroxyl groups interact with hydroxyl groups attached to the surface of the negative electrode active material, and the negative electrode active material and the binder 1 are bonded.

[0099] As for the presence ratio of the crosslinking agent 3 in the binder 1, for example, the crosslinking agent 3 is set to 5 parts by weight or more and less than 53 parts by weight relative to 100 parts by weight of the water-soluble polymer 2. In addition, as for the presence ratio of the crosslinking agent 3 in the binder 1, for example, it is preferred that the crosslinking agent 3 is set to 13 parts by weight or more and less than 28 parts by weight relative to 100 parts by weight of the water-soluble polymer 2. If the presence ratio of the crosslinking agent 3 is low, there are fewer crosslinking points in the binder 1 and the elasticity of the binder is reduced. The binder 1 with low elasticity cannot fully alleviate the volume change during charge and discharge. The negative electrode active material layer 34 containing the binder 1 with low elasticity is prone to cracking during charge and discharge. In addition, if the presence ratio of the crosslinking agent 3 is high, the proportion of hydroxyl groups that can exist freely in the binder 1 is reduced, and the bonding property with the negative electrode active material and the negative electrode collector 32 is reduced. In addition, the binder 1 with a high presence ratio of the crosslinking agent 3 has a high viscosity because of its low dispersibility in water, and sometimes gels.

[0100] The cellulose nanofibers 4 are fibers obtained by finely unraveling cellulose, which is a main component of plant fibers, into nanometer sizes. The cellulose nanofibers 4 are bonded to the water-soluble polymer 2 via the crosslinking agent 3 and are also bonded to the negative electrode active material.

[0101] The average fiber length of the cellulose nanofibers 4 is, for example, 0.1 μm or more and 1000 μm or less, preferably 1 μm or more and 750 μm or less, more preferably 1.3 μm or more and 500 μm or less, further preferably 1.4 μm or more and 250 μm or less, and particularly preferably 2.0 μm or more and 100 μm or less. When the fiber length of the cellulose nanofibers 4 is long, the flatness during coating is reduced. When the fiber length of the cellulose nanofibers 4 is short, the adhesion to the negative electrode active material is reduced.

[0102] The average fiber diameter of the cellulose nanofibers 4 is, for example, 1 nm to 10 μm, preferably 5 nm to 2.5 μm, more preferably 20 nm to 700 nm, and further preferably 30 nm to 200 nm.

[0103] The abundance ratio of the cellulose nanofibers 4 in the adhesive 1 is preferably, for example, 2% or more and 10% or less in terms of solid content, when the total of the water-soluble polymer 2 and the cellulose nanofibers 4 is 100. When the abundance ratio of the cellulose nanofibers 4 is low, the strength of the adhesive 1 decreases. When the abundance ratio of the cellulose nanofibers 4 is high, the dispersibility of the adhesive 1 in water decreases, the viscosity of the adhesive 1 increases, and the adhesive may gel.

[0104] The adhesive 1 of the present embodiment has a peak in the range of diffraction angle 2θ of 16° to 21° when subjected to wide angle X-ray scattering (WAXS) measurement using CuKα rays. The half maximum width (full width at half maximum: FWHM) of the peak is 5.5° or less.

[0105] Figure 4 This is an example of wide angle X-ray scattering (WAXS) measurement results of the adhesive agent etc. according to the first embodiment. The wide angle X-ray scattering is performed using CuKα rays. Figure 4 Shows the measurement results of four substances.

[0106] The first substance is a completely saponified polyvinyl alcohol (PVA) with a molecular weight of 80,000, which is a single film of the above-mentioned water-soluble polymer 2. The second substance is a substance obtained by mixing and heating cellulose nanofibers 4 and completely saponified polyvinyl alcohol (PVA) with a molecular weight of 80,000. The third substance is a first example of the adhesive 1 of the present embodiment. The adhesive 1 of the first example is a substance formed by crosslinking a water-soluble polymer 2 composed of completely saponified polyvinyl alcohol (PVA) with a molecular weight of 80,000, a crosslinking precursor 5 composed of blocked isocyanate (X-12-1308ES manufactured by Shin-Etsu Chemical Co., Ltd.), and cellulose nanofibers 4. The fourth substance is the second example of the adhesive 1 of the present embodiment. The binder 1 of the second example is a product obtained by cross-linking a water-soluble polymer 2 composed of completely saponified polyvinyl alcohol (PVA) having a molecular weight of 80,000, a cross-linking precursor 5 composed of titanium lactate (ORGATIX TC-315 manufactured by Matsumoto Fine Chemical Co. Ltd.), and cellulose nanofibers 4 .

[0107] The first to third substances have a peak when the diffraction angle 2θ is 19.4°, and the fourth substance has a peak when the diffraction angle 2θ is 19.5°. That is, the first to fourth substances all have a peak in the range of diffraction angle 2θ being 16° or more and 21° or less. This peak is a peak from water-soluble polymer 2. This peak is also confirmed in the third and fourth substances, indicating that water-soluble polymer 2 exists in adhesive 1.

[0108] In addition, the half-peak width of the peaks of the first to third substances is 1.5°, and the half-peak width of the peak of the fourth substance is 1.9°. That is, the half-peak widths of the peaks of the first to fourth substances are all below 5.5°. The narrow half-peak width of the peak means that the crystallinity of the adhesive 1 is high. The half-peak width of the peak in the third and fourth substances is below 5.5°, which means that the water-soluble polymer 2 is present in the adhesive 1 in a state of maintaining crystallinity. By controlling the proportion of the water-soluble polymer in the adhesive, the curing conditions of the adhesive, etc., the position and half-peak width of the peak of the adhesive 1 can be controlled.

[0109] The content of the binder in the negative electrode active material layer 34 is not particularly limited. For example, the content of the binder relative to the total mass of the negative electrode active material, the conductive aid, and the binder is 0.5 mass % or more and 20 mass % or less, preferably 5 mass % or more and 15 mass % or less. When the content of the binder is small, the bonding strength of the negative electrode 30 is weakened. When the content of the binder is high, the energy density of the lithium ion secondary battery 100 is reduced because the binder is not electrochemically active and does not contribute to the discharge capacity.

[0110] The conductive additive in the negative electrode active material layer 34 improves the electron conductivity between the negative electrode active materials. The conductive additive can be the same as that of the positive electrode active material layer 24 .

[0111] The content of the conductive aid in the negative electrode active material layer 34 is not particularly limited. For example, the content of the conductive aid relative to the total mass of the negative electrode active material, conductive aid, and binder is 5 mass % to 20 mass %, preferably 1 mass % to 12 mass %.

[0112] <Diaphragm>

[0113] The separator 10 is sandwiched between the positive electrode 20 and the negative electrode 30. The separator 10 isolates the positive electrode 20 and the negative electrode 30 to prevent a short circuit between the positive electrode 20 and the negative electrode 30. The separator 10 extends inward along the positive electrode 20 and the negative electrode 30. Lithium ions can pass through the separator 10.

[0114] The diaphragm 10 has, for example, an electrically insulating porous structure. The diaphragm 10 is, for example, a single layer or a laminate of a polyolefin film. The diaphragm 10 may also be a stretched film of a mixture of polyethylene or polypropylene. The diaphragm 10 may also be a fiber nonwoven fabric composed of at least one constituent material selected from cellulose, polyester, polyacrylonitrile, polyamide, polyethylene and polypropylene. The diaphragm 10 may also be, for example, a solid electrolyte. Solid electrolytes include, for example, polymer solid electrolytes, oxide-based solid electrolytes, and sulfide-based solid electrolytes. The diaphragm 10 may also be an inorganic coating diaphragm. The inorganic coating diaphragm is a film formed by coating the surface of the above-mentioned film with a mixture of a resin such as PVDF or CMC and an inorganic substance such as alumina or silica. The inorganic coating diaphragm has excellent heat resistance and inhibits the precipitation of transition metals dissolved from the positive electrode to the surface of the negative electrode.

[0115] <Electrolyte>

[0116] The electrolyte is sealed in the outer casing 50 and impregnated into the power generating element 40. The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolytic salt. The electrolytic salt is dissolved in the non-aqueous solvent.

[0117] A known electrolyte solution can be used as the electrolyte solution. The electrolyte solution contains, for example, a non-aqueous solvent and an electrolyte salt.

[0118] The electrolytic salt is, for example, a lithium salt. The electrolyte is, for example, LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, LiBOB, LiN(FSO2)2, etc. The lithium salt can be used alone or in combination of two or more. From the viewpoint of ionization, the electrolyte preferably contains LiPF6. The concentration of the electrolytic salt is, for example, greater than 0.8 mol / L and less than 5.0 mol / L.

[0119] The non-aqueous solvent is, for example, an aprotic organic solvent. The organic solvent is, for example, a cyclic carbonate, a chain carbonate, an ether, a mixture thereof, etc. In addition, the solvent may also be an ionic liquid.

[0120] Cyclic carbonate solvates the electrolyte. Cyclic carbonates are, for example, ethylene carbonate, propylene carbonate, butylene carbonate, and fluoroethylene carbonate. Cyclic carbonates preferably contain at least fluoroethylene carbonate. The redox potential of fluoroethylene carbonate (FEC) is high, and it is easily reduced and decomposed. Because a part of fluoroethylene carbonate (FEC) is reduced and decomposed, the electrolyte or residual solvent in the electrolyte is not easy to be decomposed. In addition, fluoroethylene carbonate (FEC) forms a thin and stable coating (SEI coating) on ​​the surface of the negative electrode active material as a whole in the initial use of lithium ion secondary batteries. The SEI coating prevents direct contact between the negative electrode active material and the electrolyte, and prevents the decomposition of the electrolyte.

[0121] The chain carbonate reduces the viscosity of the cyclic carbonate. The chain carbonate is, for example, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate. In addition, the nonaqueous solvent may also include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc.

[0122] In addition, the electrolyte may also have SEI (Solid Electrolyte Interface) forming materials, surfactants, etc. Additives include, for example, vinylene carbonate, vinyl ethylene carbonate, phenyl ethylene carbonate, succinic anhydride, lithium bis(oxalate), lithium tetrafluoroborate, dinitrile, propane sultone, butane sultone, propene sultone, 3-sulfolene, fluorinated aryl ether, fluorinated acrylate, etc.

[0123] <Exterior body>

[0124] The outer casing 50 seals the power generation element 40 and the non-aqueous electrolyte in its interior. The outer casing 50 suppresses leakage of the non-aqueous electrolyte to the outside and intrusion of moisture or the like from the outside into the lithium ion secondary battery 100 .

[0125] For example, Figure 1 As shown, the outer package 50 includes a metal foil 52 and a resin layer 54 laminated on each surface of the metal foil 52. The outer package 50 is a metal laminate film in which the metal foil 52 is applied to a polymer film (resin layer 54) from both sides.

[0126] As the metal foil 52, for example, aluminum foil can be used. The resin layer 54 can utilize a polymer film such as polypropylene. The material constituting the resin layer 54 may be different on the inside and outside. For example, as the material of the outside, a polymer with a high melting point such as polyethylene terephthalate (PET) and polyamide (PA) can be used, and as the material of the polymer film on the inside, polyethylene (PE) and polypropylene (PP) can be used.

[0127] <Terminal>

[0128] The terminals 60 and 62 are connected to the negative electrode 30 and the positive electrode 20, respectively. The terminal 62 connected to the positive electrode 20 is a positive terminal, and the terminal 60 connected to the negative electrode 30 is a negative terminal. The terminals 60 and 62 are responsible for the electrical connection between the outside and the power generation element 40. The terminals 60 and 62 are formed of a conductive material such as aluminum, nickel, and copper. The connection method can be welding or screwing. In order to prevent short circuits, the terminals 60 and 62 are preferably protected by insulating tape.

[0129] "Method for producing lithium-ion secondary battery"

[0130] The lithium ion secondary battery 100 is produced by separately preparing the negative electrode 30, the positive electrode 20, the separator 10, the electrolyte solution, and the outer casing 50, and assembling them. An example of a method for producing the lithium ion secondary battery 100 will be described below.

[0131] First, the negative electrode 30 is produced. The negative electrode 30 is produced by, for example, sequentially performing a precursor solution production step, a slurry production step, an electrode coating step, a curing step, and a rolling step.

[0132] First, a precursor solution preparation process is performed. First, a water-soluble polymer solution, a cross-linking precursor 5, and cellulose nanofibers 4 are prepared. The cross-linking precursor 5 is a cross-linking agent before cross-linking. The cross-linking precursor 5 is a titanium compound, a blocked isocyanate silane compound, a blocked diisocyanate compound, and a blocked triisocyanate compound. Next, the water-soluble polymer solution, the cross-linking precursor 5, and the cellulose nanofibers 4 are mixed to adjust the adhesive precursor solution. The mixing ratio of the water-soluble polymer solution, the cross-linking precursor 5, and the cellulose nanofibers 4 is adjusted according to the structure of the target adhesive.

[0133] Although it varies depending on the type of water-soluble polymer, when the water-soluble polymer is dissolved in water, stirring is performed for more than 2 hours at room temperature to below 100°C. The rotation speed during stirring is set to be above 550rpm and below 1500rpm to completely dissolve it. Thereafter, the cross-linked precursor 5 and the cellulose nanofiber 4 are added to the water-soluble polymer solution and stirred at room temperature for more than 5 minutes. The rotation speed during stirring is, for example, set to be above 180rpm and below 400rpm. By fully dispersing the cross-linked precursor 5 and the cellulose nanofiber 4 in the water-soluble polymer solution, the crystallinity of the cured adhesive can be improved.

[0134] Next, a slurry preparation step is performed. In the slurry preparation step, a negative electrode active material (silicon or a silicon compound) and a conductive auxiliary agent are added to a precursor solution of a binder.

[0135] The solvent is, for example, water, N-methyl-2-pyrrolidone, etc. The composition ratio of the negative electrode active material, the conductive auxiliary agent, and the binder precursor solution is, for example, 70 wt% to 100 wt%: 0 wt% to 10 wt%: 0 wt% to 20 wt% by mass ratio. These mass ratios are adjusted to 100 wt% as a whole.

[0136] The negative electrode active material may also be a material obtained by mixing and compounding active material particles and conductive materials while applying shear force. If the active material particles are mixed by applying shear force to a degree that the active material particles do not deteriorate, the surface of the active material particles is coated with the conductive material. In addition, the particle size of the negative electrode active material can be adjusted by the degree of mixing. In addition, the negative electrode active material after preparation may be sieved to make the particle size uniform.

[0137] Next, an electrode coating step is performed. The electrode coating step is a step of coating the slurry on the surface of the negative electrode current collector 32. The slurry coating method is not particularly limited. For example, a slit die coating method or a doctor blade method can be used as the slurry coating method.

[0138] Next, a curing process is performed. In the curing process, the slurry is annealed. The water-soluble polymer 2, the crosslinking agent 3, and the cellulose nanofibers 4 are crosslinked by annealing the slurry. In addition, in the curing process, the solvent is removed. The curing process is performed, for example, in a nitrogen atmosphere. The curing temperature is, for example, set to be above 120°C and below 150°C. In addition, the heating rate to reach the curing temperature is, for example, set to be above 2°C / minute and below 5°C / minute. In addition, the cooling rate after curing is, for example, set to be above 2°C / minute and below 5°C / minute. As described above, the position and half-peak width of the peak in the wide-angle X-ray scattering (WAXS) measurement results of the cured adhesive can be controlled by the following steps: in the precursor solution preparation step, the crosslinking precursor 5 and the cellulose nanofibers 4 are fully dispersed in the water-soluble polymer solution; the mixing ratio of the water-soluble polymer 2, the crosslinking precursor 5, and the cellulose nanofibers 4 in the adhesive is adjusted; and the adhesive is cured under the above conditions.

[0139] The rolling step is performed as necessary. The rolling step is a step of applying pressure to the negative electrode active material layer 34 to adjust the density of the negative electrode active material layer 34. The rolling step is performed by, for example, a roll press device.

[0140] The positive electrode 20 can be produced by the same steps as the negative electrode 30. Commercially available products can be used for the separator 10 and the outer casing 50.

[0141] Next, these are stacked so that the separator 10 is located between the prepared positive electrode 20 and negative electrode 30 to prepare the power generation element 40. When the power generation element 40 is a wound body, the positive electrode 20, the negative electrode 30, and the separator 10 are wound around one end side of the axis.

[0142] Finally, the power generation element 40 is sealed in the outer casing 50. The non-aqueous electrolyte is injected into the outer casing 50. The non-aqueous electrolyte is impregnated into the power generation element 40 by reducing the pressure, heating, etc. after the injection of the non-aqueous electrolyte. The outer casing 50 is sealed by applying heat, etc. to obtain the lithium ion secondary battery 100. It should be noted that the power generation element 40 may be impregnated in the electrolyte without injecting the electrolyte into the outer casing 50.

[0143] The lithium ion secondary battery 100 of the first embodiment has excellent cycle characteristics. It is believed that this is because the binder contained in the negative electrode active material layer 34 is high in strength and high in elasticity. By maintaining the crystallinity of the water-soluble polymer, the binder becomes high in strength and high in elasticity. It can be confirmed that this is because the wide-angle X-ray scattering (WAXS) measurement result of the binder 1 has a specified peak. The crosslinking agent 3 is preferentially adsorbed on the cellulose nanofibers 4. Therefore, it is also believed that the excessive reaction of the crosslinking agent 3 and the water-soluble polymer 2 is suppressed, and the water-soluble polymer 2 with high crystallinity is maintained in the binder 1. In addition, the water-soluble polymer is crosslinked by the crosslinking agent 3 having a small crystalline structure, so that the binder 1 becomes high in strength and high in elasticity.

[0144] As described above, the embodiments of the present invention are described in detail with reference to the drawings, but each structure of each embodiment and their combination are merely examples, and addition, omission, replacement and other changes of structures can be made without departing from the scope of the present invention.

[0145] Example

[0146] "Example 1"

[0147] First, a precursor solution of an adhesive is prepared. First, 100 parts by mass of a water-soluble polymer and water are added and stirred at room temperature for more than 2 hours. The rotation speed during stirring is set to be above 550 rpm and below 1500 rpm. Then, stir until the water-soluble polymer is completely dissolved in water. Afterwards, 3 parts by mass of a cross-linked precursor and 10 parts by mass of cellulose nanofibers are added to the water-soluble polymer aqueous solution. The solution is stirred at room temperature at a rotation speed of 300 rpm for more than 5 minutes. The water-soluble polymer uses carboxymethyl cellulose with a molecular weight of 90,000. The cross-linked precursor uses titanium lactate (ORGATIX TC-315 manufactured by Matsumoto Fine Chemical Co. Ltd.). The cellulose nanofiber uses the Rheocrysta I-2SX standard grade manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0148] Next, the negative electrode active material and the conductive additive are added to the binder precursor solution. The negative electrode active material is SiO obtained by a disproportionation reaction through a heat treatment at 1000°C under reduced pressure. x The conductive aid was set to Super-P (registered trademark). Then, 25 g of the negative electrode active material, 1.4 g of the conductive aid, and 13.5 g of the binder precursor solution (solid content concentration 10%) were mixed to adjust the coating liquid (slurry). The total solid content concentration in the coating liquid was 35 wt %. Next, the slurry was applied to the copper foil as the negative electrode collector using a doctor blade.

[0149] Next, the negative electrode current collector coated with the slurry is annealed in a nitrogen atmosphere. The annealing is performed under the following conditions: the temperature is raised at 5°C / min, maintained at 150°C for 2 hours, and the temperature is lowered at 5°C / min. By annealing, the water-soluble polymer, the crosslinking agent, and the cellulose nanofibers are crosslinked, and the slurry is solidified. Then, the negative electrode current collector after the slurry is solidified is rolled to form the negative electrode active material layer 34. The negative electrode is produced by punching the negative electrode current collector and the negative electrode active material layer 34 into an electrode size of 22×32 mm using a mold.

[0150] Here, a binder precursor solution was prepared under the same conditions as above, and the binder precursor solution was annealed to prepare a binder (not containing a negative electrode active material and a conductive auxiliary agent). The binder was subjected to wide-angle X-ray scattering measurement using CuKα rays. The diffraction angle 2θ of the binder of Example 1 was 16.2°, and the half-peak width was 3.3°.

[0151] The positive electrode active material uses Li x CoO2. Ketjen black was used as a conductive aid. Polyvinylidene fluoride (PVDF) was used as a binder. N-methyl-2-pyrrolidone was used as a solvent. 96 parts by mass of a positive electrode active material, 2 parts by mass of a conductive aid, 2 parts by mass of a binder, and 70 parts by mass of a solvent were mixed to prepare a positive electrode slurry. Then, the positive electrode slurry was applied to one side of an aluminum foil having a thickness of 15 μm, vacuum dried at 100°C and rolled for 2 hours, thereby forming a positive electrode active material layer 24. Then, a mold was used to punch out the positive electrode collector and the positive electrode active material layer 24 according to an electrode size of 22×32 mm to prepare a positive electrode.

[0152] Next, an electrolyte solution was prepared. The solvent used was a mixture of ethylene carbonate (EC): diethyl carbonate (DEC) = 3:7 in mass ratio. LiPF6 was used as an electrolytic salt. The concentration of LiPF6 was set to 1 mol / L.

[0153] (Preparation of lithium-ion secondary battery for evaluation)

[0154] The produced negative electrode and positive electrode are stacked via a diaphragm (porous polyethylene sheet) in a manner that the positive electrode active material layer and the negative electrode active material layer are opposite to each other to obtain a laminate. A nickel negative electrode lead is installed on the negative electrode of the laminate. An aluminum positive electrode lead is installed on the positive electrode of the laminate. The positive electrode lead and the negative electrode lead are welded by an ultrasonic welding machine. The laminate is inserted into an outer casing of an aluminum laminate film, and the surrounding parts except one are heat-sealed to form a closed portion. Then, the above-mentioned electrolyte is finally injected into the outer casing, and then the remaining one is sealed by heat sealing while being depressurized by a vacuum sealing machine to produce a lithium-ion secondary battery.

[0155] (Determination of capacity retention after 200 cycles)

[0156] The cycle characteristics of the lithium ion secondary battery were measured using a secondary battery charge and discharge tester (manufactured by Hokuto Denko Co., Ltd.).

[0157] The battery was charged at a constant current rate of 0.5C (the current value at which charging is completed within 1 hour at 25°C) until the battery voltage reached 4.2 V, and discharged at a constant current rate of 1.0C until the battery voltage reached 2.5 V. The discharge capacity after the charge and discharge was detected, and the battery capacity Q1 before the cycle test was calculated.

[0158] The battery whose battery capacity Q1 was obtained in the above was charged again using a secondary battery charge and discharge test device at a constant current charge of 0.5C until the battery voltage became 4.2V, and discharged at a constant current discharge of 1.0C until the battery voltage became 2.5V. The above charge and discharge were counted as 1 cycle, and 200 cycles of charge and discharge were performed. After that, the discharge capacity after 200 cycles of charge and discharge was detected, and the battery capacity Q2 after 200 cycles was obtained.

[0159] The capacity retention rate E after 200 cycles was determined from the capacities Q1 and Q2 determined above. The capacity retention rate E was determined by E=Q2 / Q1×100. The capacity retention rate of Example 1 was 66%.

[0160] "Examples 2 to 66"

[0161] In Examples 2 to 66, any one of the type of water-soluble polymer, the type of crosslinking precursor, the mass ratio of the crosslinking precursor to the water-soluble polymer, and the mass ratio of the cellulose nanofiber to the water-soluble polymer was changed, which is different from Example 1. In addition, when polyvinyl alcohol was used as the water-soluble polymer, it was dissolved at 100° C. to obtain a polyvinyl alcohol aqueous solution, which is different from Example 1. The peak position and half-peak width of the binder and the capacity retention rate were obtained in the same manner as in Example 1 under the other conditions.

[0162] "Comparative Example 1"

[0163] Comparative Example 1 differs from Example 1 in that no crosslinking precursor and cellulose nanofibers were added when preparing the binder. The other conditions were the same as in Example 1, and the peak position and half peak width of the binder and the capacity retention rate were determined.

[0164] "Comparative Example 2"

[0165] Comparative Example 2 differs from Example 1 in that no crosslinking precursor was added when preparing the binder. The other conditions were the same as in Example 1, and the peak position and half peak width of the binder and the capacity retention rate were determined.

[0166] "Comparative Example 3"

[0167] Comparative Example 3 differs from Example 1 in that the mass ratio of the crosslinking precursor to the water-soluble polymer and the mass ratio of the cellulose nanofiber to the water-soluble polymer were changed when preparing the binder. The peak position and half-peak width of the binder and the capacity retention rate were obtained in the same manner as in Example 1 under other conditions.

[0168] "Examples 67-72"

[0169] Examples 67 to 72 differ from Example 1 in that the water-soluble polymer was polyacrylic acid and any of the type of crosslinking precursor, the mass ratio of the crosslinking precursor to the water-soluble polymer, and the mass ratio of the cellulose nanofiber to the water-soluble polymer were changed. The peak position and half-peak width of the binder and the capacity retention rate were obtained in the same manner as in Example 1 under the other conditions.

[0170] The results of Examples 1 to 72 and Comparative Examples 1 to 3 are summarized in Tables 1 to 5. TC-300 in the table refers to ORGATIX TC-300 manufactured by Matsumoto Fine Chemical Co. Ltd. TC-300 is ammonium lactate titanium. Similarly, TC-315 in the table refers to ORGATIX TC-315 manufactured by Matsumoto Fine Chemical Co. Ltd. TC-315 is titanium lactate. In addition, Mw in the table is the weight average molecular weight of the water-soluble polymer. In addition, X-12-1308ES in the table is a blocked isocyanate manufactured by Shin-Etsu Chemical Co., Ltd. In addition, blocked diphenylmethane-4,4-diisocyanate is a blocked diisocyanate. In addition, 1,3,5-tris(isocyanatomethyl)benzene and 1,3,5-tris(6-isocyanatohexyl)biuret are blocked triisocyanates.

[0171]

[0172]

[0173]

[0174]

[0175] [Table 5]

[0176]

[0177] Compared with Comparative Examples 1 to 3, the lithium ion secondary batteries using the binder in Examples 1 to 72 still showed high capacity retention after 200 cycles and high cycle characteristics. In Comparative Example 1, the binder had no electrolyte resistance and the battery characteristics could not be evaluated. In Comparative Examples 2 and 3, the mechanical strength of the binder was not sufficient and sufficient cycle characteristics were not obtained.

Claims

1. A cured product for a lithium ion secondary battery, wherein: The cured product for lithium ion secondary battery comprises a water-soluble polymer, a crosslinking agent, and cellulose nanofibers. The cross-linking agent cross-links different water-soluble polymers or between the water-soluble polymer and the cellulose nanofibers. In wide-angle X-ray scattering WAXS measurement using CuKα rays, there is a peak in the range of a diffraction angle 2θ of 16° or more and 21° or less. The half-value width of the peak is 5.5° or less.

2. The cured product for lithium ion secondary battery according to claim 1, wherein The water-soluble polymer is any one or more selected from polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, a copolymer of acrylic acid and vinyl alcohol, and polyacrylic acid.

3. The cured product for lithium ion secondary battery according to claim 1, wherein The crosslinking agent is: a compound obtained by dissociating a blocking agent from any one selected from a blocked isocyanate silane compound, a blocked diisocyanate compound, and a blocked triisocyanate compound; or a titanium compound.

4. The cured product for lithium ion secondary battery according to claim 1, wherein The water-soluble polymer has a weight average molecular weight of 9,000 or more and 200,000 or less.

5. A negative electrode for a lithium ion secondary battery, wherein: A secondary battery having a negative electrode active material and the cured product according to claim 1.

6. A lithium ion secondary battery, wherein: A lithium ion secondary battery comprising the negative electrode for lithium ion secondary battery according to claim 5, a positive electrode, and a separator located between the negative electrode for lithium ion secondary battery and the positive electrode.

Citation Information

Patent Citations

  • Vacuum pump and exhaust system

    JP2022145039A

  • Electrode slurry, electrode, manufacturing method thereof, and secondary battery

    WO2018135352A1